Dynamics of pleasure-displeasure at the limit of exercise tolerance: conceptualizing the sense of exertional physical fatigue as an affective response - Hartman, M. E.; Ekkekakis, P.; Dicks, N. D.; Pettitt, R. W. (The Journal of Experimental Biology, 2019)
The search for variables involved in the regulation and termination of exercise performance has led to integrative models that attribute a central role to the brain and utilize an array of psychological terms (e.g. sensation, perception, discomfort, tolerance). We propose that theorizing about exercise regulation would benefit from establishing cross-disciplinary bridges to research fields, such as affective psychology and neuroscience, in which changes along the dimension of pleasure-displeasure are considered the main channel via which homeostatic perturbations enter consciousness and dictate corrective action (slowing down or stopping). We hypothesized that ratings of pleasure-displeasure would respond to the severity of homeostatic perturbation and would be related to time to exhaustion during exercise performed at an unsustainable intensity. In a within-subjects experiment (N=15, 13 men and 2 women, age 23.4±2.2 years; maximal oxygen uptake 46.0±8.0 ml kg-1 min-1), we compared the slope of ratings of pleasure-displeasure (acquired every 1 min) during cycling exercise at a power output 10% above critical power until volitional termination under glycogen-loaded and glycogen-depleted conditions. As hypothesized, ratings of pleasure-displeasure declined more steeply under glycogen depletion (P=0.009, d=0.70) and correlated closely with time to exhaustion under both glycogen-loaded (r=0.85; P<0.001) and glycogen-depleted conditions (r=0.83; P<0.001). We conclude that in exercise, as in other domains, changes in pleasure-displeasure may be the main channel via which homeostatic perturbations enter consciousness. This proposal may have important implications for conceptualizing and identifying the neurobiological mechanisms of the sense of exertional physical fatigue.